Empowering Young Indonesian Readers: The Effectiveness of CSR in a Rural Junior High School - Lailan Khairi; Indawan Alfaresi (Explorations in English Learning, 2025)
Reading comprehension is a fundamental component of language proficiency and academic success, yet many EFL learners struggle to understand texts due to limited strategic reading instruction. This study investigates the effectiveness of the Collaborative Strategic Reading (CSR) technique in enhancing reading comprehension among eighth-grade students in an Indonesian junior high school context. Employing a pre-experimental one-group pretest-posttest design, the research involved 33 students selected through cluster random sampling. Data were collected using a multiple-choice reading comprehension test administered before and after the intervention. The results were analyzed using SPSS 17.0, with descriptive and inferential statistics including normality, homogeneity, and paired-sample t-tests. Findings revealed a statistically significant improvement in post-test scores (M = 17.18, SD = 3.24) compared to pre-test scores (M = 14.12, SD = 3.20), with a p-value of < 0.001. These results suggest that CSR is an effective instructional strategy for improving EFL learners’ reading comprehension. The study highlights the potential of CSR to foster strategic reading behaviors, promote student collaboration, and support more meaningful engagement with texts. Implications for classroom practice and suggestions for further research are discussed.